KERINGANAN HUKUMAN BAGI SAKSI YANG BEKERJASAMA (JUSTICE COLLABORATOR) DALAM KASUS PEMBUNUHAN BERENCANA (STUDI PUTUSAN NOMOR. 798/Pid.B/2022/PN.Jkt.Sel.) - Putra, Verdy Cahyana; Firmansyah, Hery (UNES Law Review, 2023)
In the case of premeditated murder committed by Former Head of Propam Polri Ferdy Sambo division which was carried out at Ferdy Sambo's official house on Jalan Duren Tiga, No. 46, South Jakarta on Friday (8/7/2022) at around 17.00 WIB against Brigadier Joshua Hutabarat. In the premeditated murder case, Bharada Richard Eliezer, who acted as a justice collaborator, made it easier for law enforcement officials to uncover the case, in which a justice collaborator was given a very light sentence compared to the sentence previously given by the Public Prosecutor, namely imprisonment for 12 years. however, when the verdict was passed against Bharada Richard Eliezer, the Panel of Judges at the South Jakarta District Court only gave a sentence in the form of imprisonment for 1 (one) year and 6 (six) months against Bharada Richard Eliezer, who was the perpetrator of the premeditated murder. The court judges gave Bharada Richard Eliezer a light sentence because he was a justice collaborator who uncovered the premeditated murder case of Brigadier Joshua Hutabarat, in SEMA No. 4 of 2011, namely a justice collaborator, was given a lighter sentence than the perpetrators of other crimes involved. on the crime of premeditated murder.